One hand open palm technique for infant CPR - Patel, Shruti; Balikai, Shilpa; Elgin, Timothy G.; Newell, Elizabeth A.; Colaizy, Tarah T.; Raghavan, Madhavan L.; Atkins, Dianne L.; Haskell, Sarah E. (Frontiers in Disaster and Emergency Medicine, 2023)
BACKGROUND Guideline recommended chest compression depth, rate and recoil are essential factors for return of spontaneous circulation (ROSC) in cardiopulmonary resuscitation (CPR). A pediatric resuscitation collaborative recently demonstrated that healthcare providers fail to meet the American Heart Association (AHA) guidelines, with greatest difficulty in achieving chest compression depth targets in infants. We hypothesized that use of heel of one hand (open palm technique, OPT) will increase chest compression depth in infants compared to standard CPR techniques [two-finger technique (TFT), two thumb-encircle-hand technique (TTT)]. METHODS A prospective, randomized, single-center study was completed using an infant manikin. Thirty pediatric critical care providers performed 2 minutes of CPR for each technique followed by 5 minutes rest. Each participant completed a survey at the end measuring difficulty level to assess feasibility of this new technique. RESULTS Mean chest compression depth for OPT was significantly deeper compared to TFT (2.61± 0.63 cm vs 2.25 ± 0.54 cm, p= 0.0004) but not significantly deeper compared to TTT (2.43 ± 0.46 cm, p= 0.0820). OPT was graded as easiest technique followed by TTT (2.20 ± 0.76 vs 3.17 ± 0.95, p < 0.0001), then TFT (3.38 ± 0.83, p < 0.0001). CONCLUSION OPT for infant CPR resulted in improved chest compression depth. OPT was considered the easiest technique compared to standard infant CPR techniques, thus making it feasible to perform. Importantly, all providers failed to meet the AHA infant chest compression depth goal of 4 centimeters regardless of technique. Future research is needed to optimize CPR technique and performance to achieve targeted chest compression depth in infants.